Association of PTPRD/PTPRT Mutation With Better Clinical Outcomes in NSCLC Patients Treated With Immune Checkpoint Blockades - Wang, Xiaoyan; Wu, Bingchen; Yan, Zhengqing; Wang, Guoqiang; Chen, Shiqing; Zeng, Jian; Tao, Feng; Xu, Bichun; Ke, Honggang; Li, Mei (Frontiers in Oncology, 2021)
The common gamma receptor–dependent cytokines and their JAK-STAT pathways play important roles in T cell immunity and have been demonstrated to be related with response to immune checkpoint blockades (ICBs). PTPRD and PTPRT are phosphatases involved in JAK-STAT pathway. However, their clinical significance for non-small cell lung cancer (NSCLC) treated with ICBs is still unclear. Genomic and survival data of NSCLC patients administrated with anti–PD-1/PD-L1 or anti–CTLA-4 antibodies (Rizvi2015; Hellmann2018; Rizvi2018 Samstein2019) were retrieved from publicly accessible data. Genomic, survival and mRNA data of 1007 patients with NSCLC were obtained from The Cancer Genome Atlas (TCGA). PTPRD/PTPRT mutation was significantly associated with better progression-free survival (PFS) in three independent Rizvi2015, Hellmann2018 and Rizvi2018 cohorts. The median PFS for PTPRD/PTPRT mutant-type vs. wild-type NSCLC patients were not reached vs. 6.3 months (Rizvi2015, HR = 0.16; 95% CI, 0.02-1.17; P=0.03), 24.0 vs. 5.4 months (Hellmann2018, HR, 0.49; 95% CI, 0.26-0.94; P=0.03), 5.6 vs. 3.0 months (Rizvi2018, HR = 0.64; 95% CI, 0.44-0.92; P=0.01) and 6.8 vs. 3.5 months (Pooled cohort, HR, 0.54; 95% CI, 0.39-0.73; P<0.0001) respectively. PTPRD/PTPRT mutation was an independent predictive factor for PFS in pooled cohort (P = 0.01). Additionally, PTPRD/PTPRT mutation associated with better overall survival (OS) in Samstein2019 cohort (19 vs. 10 months, P=0.03). While, similar clinical benefits were not observed in patients without ICBs treatment (TCGA cohort, P=0.78). In the further exploratory analysis, PTPRD/PTPRT mutation was significantly associated with increased tumor mutation burden and higher mRNA expression of JAK1 and STAT1. Gene Set Enrichment Analysis revealed prominent enrichment of signatures related to antigen processing and presentation in patients with PTPRD/PTPRT mutation. This work suggested that PTPRD/PTPRT mutation might be a potential positive predictor for ICBs in NSCLC. These results need to be further confirmed in future.